A chromosome-scale genome assembly of the nipa palm hispid beetle Octodonta nipae - Baozhen Tang; Chuanlin Yin; Kang He; Shaomin Tao; Lang Fu; Ying Liu; Fei Li; Youming Hou (Scientific Data, 2024)
Abstract Nipa palm hispid beetle (Octodonta nipae) is an insect species that is native to Malaysia but has spread to southern China and beyond, seriously threatening palm production. A lack of high-quality genome resources has hindered understanding of the insect’s invasive characteristics and ecological adaptations. Here, we combined Illumina short read, PacBio long-read, and high-throughput chromosome conformation capture (Hi-C) sequencing technologies to generate a high-quality, chromosome-scale genome assembly of nipa palm hispid beetle. The genome assembly was 1.31 Gb in size, consisting of nine chromosomes. The contig and scaffold N50 values were 1.022 Mb and 148.6 Mb, respectively. The genome assembly completeness was estimated at 99.1%. Annotation revealed 16,305 protein-coding genes and 62.16% repeat sequences. This high-quality genome assembly is a valuable resource that will contribute to understanding of the genetic factors underlying the invasive characteristics of nipa palm hispid beetle, ultimately promoting development of efficient control policies.